Sobre la crítica foucaultiana al tema trascendental - Díaz Marsá, Marco A. (Revista de Filosofía, 2010)
We present the foucaultian critique of the transcendental theme. We will try to show, sharpening the layout of the problem, that the specific target of such critique is not so much the transcendental instance as such, present in a sui generis way in Foucault himself, as rather a certain interpretation of this instance, mastered by the “knowledge” scheme and its postulates of natural affinity, constituent subjectivity and transcendental theology. So we will determine, in the first place, the framework and reach of such critique. Secondly, we will set forth the interpretation of the transcendental which rules in the foucaultian critique of this theme. In the third place, we will take into account the assumptions which rule in this interpretation. Finally, we will sketch the foucaultian idea of “knowledge” (savoir).